2011
DOI: 10.1364/boe.2.002623
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of human skin anisotropy by polarization-sensitive optical coherence tomography

Abstract: We performed an in vivo three-dimensional analysis of anisotropic changes in the dermal birefringence of mechanically deformed human skin using polarization-sensitive optical coherence tomography (PS-OCT). The papillary-dermal birefringence of the forehead increased significantly when the skin was shrunk parallel to the body axis, and decreased significantly when the skin was shrunk perpendicular to the body axis. En-face images of the papillary-dermal birefringence revealed variations among individual subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…Almost all previous PS-OCT studies used phase retardation imaging to investigate collagen-related skin alteration and optical properties, such as age-related alteration and photo-aging [19], and some mechanical skin properties [52]. Because birefringence imaging enables a more accurate and quantitative evaluation of tissue property than the phase retardation images [22], it will enable further investigation of skin properties, alteration, and pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all previous PS-OCT studies used phase retardation imaging to investigate collagen-related skin alteration and optical properties, such as age-related alteration and photo-aging [19], and some mechanical skin properties [52]. Because birefringence imaging enables a more accurate and quantitative evaluation of tissue property than the phase retardation images [22], it will enable further investigation of skin properties, alteration, and pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of Fourier-domain OCT, including spectral-domain OCT (SD-OCT) and swept-source OCT (SS-OCT), can provide a high imaging sensitivity in biological tissue [18][19][20][21][22][23]. Currently, OCT has become a clinical approach for various disease diagnoses, such as ophthalmology [24-27], dermatology [28][29][30][31][32][33][34][35][36], cardiology [37,38], and gastrointestinal tract [39,40]. For dermatology applications, some groups have demonstrated that OCT can be used for diagnoses of skin diseases, skin cancer [28,29], sun damage [30], and burn depth [31].…”
Section: Introductionmentioning
confidence: 99%
“…For dermatology applications, some groups have demonstrated that OCT can be used for diagnoses of skin diseases, skin cancer [28,29], sun damage [30], and burn depth [31]. With polarization-sensitive OCT, the human burn scars can be quantitatively analyzed, and human skin at different ages can be differentiated [32][33][34][35]. Moreover, OCT-based angiography has been used for identification of skin diseases [36].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from three-dimensionally reconstructing the microstructures of biological tissue, there has been intensive development of functional imaging abilities, such as angiography [32][33][34][35][36][38][39][40][41][42][43][44], birefringence [45,46], and spectroscopic properties [47,48]. In the past decade, numerous groups have focused on the development of angiography techniques based on OCT, including phase-resolved Doppler OCT (PRDOCT) [32,33], scattering optical coherence angiography [34,35], speckle variance [36,[38][39][40], optical micro-angiography [41,42], and correlation mapping method [43,44].…”
Section: Introductionmentioning
confidence: 99%